How Shia Media Reported the Palestinian-Israeli Conflict? : A Critical Discourse Analysis on ahlulbaitindonesia.or.id’s News Narrative - Nawwaf, Aufa Varrassyah; Alfi, Ahmad Musonnif (DINIKA : Academic Journal of Islamic Studies, 2026)
Due to the limited studies on the minorities’ perceptions of the Palestinian-Israeli conflict, this study examines how Shia, as a minority group in Indonesia, perceive this issue. It analyzes the construction of discourse in several news articles related to the Palestinian-Israeli conflict, published in October 2024 on Shia’s website, ahlulbaitindonesia.or.id. This study is a digital or virtual ethnography that uses a qualitative approach and employs Van Dijk’s Critical Discourse Analysis theory, which requires the exploration of three dimensions: text, social cognition, and context. This study examines relevant news content retrieved using three keywords: ‘Zionis’, ‘Israel’, and ‘Palestina’, and uncovers the motivations underlying the production of discourse through an interview. This study finds that the news discourses are reported in a non-objective manner. The author has a negative tendency towards Israel by emphasizing words with the meaning of violence, disrespect, or terror. Meanwhile, Palestine was portrayed as an oppressed and honorable party. Social cognition analysis reveals that ideological and emotional factors drive the negative tendency. There is also an attempt to associate with the Shia global hub, surpassing the objective of maintaining local existence. From a contextual perspective, the massive production of negative news is a reaction to the death of three resistance figures against Israel and a response to global silence on this conflict. Ultimately, this article evaluates, amends, and refines Schäfer’s study, which merely contends that Shia entered the virtual world and utilized digital media to build a good image, whereas the phenomenon is, in fact, more complex.